Comparisons between mix designs towards SF-OPSC mechanical properties - Azmira, Ab Aziz (2015)
Oil Palm Shell (OPS) is a waste lightweight aggregate originating from the palm oil industry. In this study, OPS was used as coarse aggregate. This research investigate the comparison between mix designs towards the Steel Fiber Oil Palm Shell Concrete (SFOPSC) mechanical properties with similar concrete strength. The objectives of this study are determine the effect of different mix designs to the behaviour of SF-OPSC and study the mechanical properties of SF-OPSC. The testing specimen are cube, cylinder and prism specimens. The size of cube is 100 mm x 100 mm x 100 mm, cylinder with 150 mm in diameter and 300 mm in height and prism with the crosssection of 100 mm x 100 mm and 500 mm in length. The concrete grade that is used is 25 MPa. The tests that are conducted are compressive strength test, flexural strength test, tensile strength test and modulus of elasticity test. The type of fiber that is used is hooked end steel fiber. The volume fraction of SF is same which is 1%. The mix designs used are different in W/C; which are 0.58 and 0.62. The amount of OPS aggregate that are used in the specimen are 50% and 100%. Results shows that W/C does influenced the mechanical properties of SF-OPSC. The compressive strength of SF-OPSC increased with the increasing of W/C. While, the flexural strength increased with the increasing of W/C. Other than that, the splitting tensile strength of SF-OPSC decreased with the increasing of W/C. Finally, the W/C does influenced the modulus of elasticity of SF-OPSC.